Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1001/jamaoncol.2017.4771
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Lung Immune Prognostic Index With Immune Checkpoint Inhibitor Outcomes in Patients With Advanced Non–Small Cell Lung Cancer

Abstract: Pretreatment LIPI, combining dNLR greater than 3 and LDH greater than ULN, was correlated with worse outcomes for ICI, but not for chemotherapy, suggesting that LIPI can serve as a potentially useful tool when selecting ICI treatment, raising the hypothesis that the LIPI might be useful for identifying patients unlikely to benefit from treatment with an ICI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
761
7
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 672 publications
(803 citation statements)
references
References 34 publications
29
761
7
6
Order By: Relevance
“…A recent study demonstrated that high NLR and LDH correlated with poor outcomes after ICB treatment in lung cancer . It has also been reported that the efficacy of ICB treatment depends on suitable immune phenotypes .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A recent study demonstrated that high NLR and LDH correlated with poor outcomes after ICB treatment in lung cancer . It has also been reported that the efficacy of ICB treatment depends on suitable immune phenotypes .…”
Section: Resultsmentioning
confidence: 98%
“…). After categorizing patients using previously described cut‐off values for NLR and LDH, we found that both high NLR and LDH groups exhibited lower clonotype and diversity (Supporting Information Fig. S7).…”
Section: Resultsmentioning
confidence: 99%
“…Although many biomarkers for ICI treatment have been previously verified, most cannot be used in the real‐world clinical setting because they require specialized equipment or are too expensive to analyze. A recent study explored prognostic indexes based on pretreatment derived neutrophil‐to‐lymphocyte ratios and lactate dehydrogenase in patients with advanced NSCLC treated with ICIs …”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of NLR and ANC during nivolumab treatment may be associated with the efficacy of the subsequent salvage chemotherapy. Many studies have shown that low baseline NLR and ANC predict the efficacy of nivolumab therapy in various cancers . More recent studies have shown that an early decrease in NLR during treatment with PD‐1 inhibitors predicts its efficacy .…”
Section: Discussionmentioning
confidence: 99%